2016
DOI: 10.1186/s12859-016-1406-x
|View full text |Cite
|
Sign up to set email alerts
|

Combining independent de novo assemblies optimizes the coding transcriptome for nonconventional model eukaryotic organisms

Abstract: BackgroundNext-generation sequencing (NGS) technologies are arguably the most revolutionary technical development to join the list of tools available to molecular biologists since PCR. For researchers working with nonconventional model organisms one major problem with the currently dominant NGS platform (Illumina) stems from the obligatory fragmentation of nucleic acid material that occurs prior to sequencing during library preparation. This step creates a significant bioinformatic challenge for accurate de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…Read qualities were assessed using FastQC (Andrews, 2014), and Trimmomatic (Bolger et al, 2014) was used to remove low quality reads and adapter sequences. Reads were assembled de novo using our recently developed assembly pipeline (Cerveau and Jackson, 2016). Briefly, we employed three assembly packages with unique assembly strategies: Trinity V2.0.3 (Haas et al, 2013), CLC Genomics Workbench (www.qiagenbioinformatics.com) and IDBA-tran V1.1.1 (Peng et al, 2013).…”
Section: Library Preparation Rna Sequencing and Sequence Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Read qualities were assessed using FastQC (Andrews, 2014), and Trimmomatic (Bolger et al, 2014) was used to remove low quality reads and adapter sequences. Reads were assembled de novo using our recently developed assembly pipeline (Cerveau and Jackson, 2016). Briefly, we employed three assembly packages with unique assembly strategies: Trinity V2.0.3 (Haas et al, 2013), CLC Genomics Workbench (www.qiagenbioinformatics.com) and IDBA-tran V1.1.1 (Peng et al, 2013).…”
Section: Library Preparation Rna Sequencing and Sequence Assemblymentioning
confidence: 99%
“…Quality filtering of raw reads resulted in 34,592,975 paired end reads that were assembled as described by Cerveau and Jackson (2016), see Methods section. The assembly generated 91,443 contigs with an average length of 933 bp and an N50 value of 1,307 ( Table 1).…”
Section: Transcriptome Characterizationmentioning
confidence: 99%
“…Further, Trinity performed well for identifying isoforms of genes and excelled at assembling highly expressed genes (Honaas et al, 2016). Conversely, Cerveau and Jackson (2016) found that Trinity, CLC Bio and IDBA-Tran assemblies all contain errors introduced by the assembly algorithms. Using a combination of all three assemblers yielded a final assembly closer to biological reality than any individual assembler, when no reference genome is available (Cerveau and Jackson, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Using a combination of all three assemblers yielded a final assembly closer to biological reality than any individual assembler, when no reference genome is available (Cerveau and Jackson, 2016). As our present study used Trinity exclusively, it may be subject to the type of errors found by Cerveau and Jackson (2016) which could affect downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The alignments generated by the HISAT2 were then used to assemble the transcriptomes using StringTie or Trinity. To reduce redundancy while keeping the relevant biological information we used the script concatenator.pl (34) with the three separate assemblies as input. The script performed intra-assembly clustering with CD-HIT-EST (35), the unique transcripts from the assemblies were concatenated, and ORFs were predicted using TransDecoder ver.3.0.1 (http://transdecoder.github.io).…”
Section: Transcriptome Assembly and Quality Assessmentmentioning
confidence: 99%